A Formal Political Economy: A Critique on the Book Political Economy of the Islamic Republic - Saeed Attar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The political economy approach means analyzing the political roots of economic performance. The main purpose of this article is to review and evaluate the most important strengths and weaknesses of the book "Political Economy of the Islamic Republic" by Bahman Ahmadi Amoui. In the framework of political economy analysis, the book tries to examine the orientations and practices of the Iranian economy in the 1981s and 1991s. The book is prepared in 6 chapters and includes a series of interviews with 6 decision-makers of the Iranian economy in that period. In the first half of this article, I first introduce the book in general. Then, the advantages and disadvantages of the book along with its content advantages are examined. In the second half of the article, the content of the book is reviewed and critiqued. In this section, the components of an "in-depth analysis of the political economy of the Islamic Republic" are examined. This paper is analytical research with a critical approach through a case study of the book.